Optical code division multiple access codes comparison in free space optics and optical fiber transmission medium - Moghaddasi, Majid; Seyedzadeh, Saleh; Ahmad Anas, Siti Barirah (IEEE, 2014)
Performance of three different Optical Code Division Multiple Access codes namely Prime Code (PC), Quadratic Congruence (QC), and Khazani-Syed (KS) code are compared in Free Space Optic (FSO) and optical fiber transmission. The simulation results show that efficiency of a code family is medium-dependent. While one code family performs the best in fiber medium, it is not necessary that it acts the same in FSO. For instance, KS with code weight of 6 provides BER 10-12 at 600 m distance, while other codes cannot even reach to the threshold 10-9 at this point. However this code shows vulnerability against fiber dispersion. At 5 km fiber, it provides BER of 10-7, even less then PC with 10-8. In that point KS code with weight 6 attains the best performance with BER of 10-11.